Review of the genus Sympagus Bates, 1881 (Coleoptera: Cerambycidae: Lamiinae: Acanthocinini) - Hovore, Frank T.; Toledo, Víctor H. (Zootaxa, 2006)
The genus Sympagus Bates, 1881, is redescribed and redefined, with two species described as new, S. cedrelis, from Mexico and Guatemala, and S. monnei, from Panama. The genus Stenopsilus Gilmour, 1959, is synonymized with Sympagus, creating Sympagus bimaculatus, new combination. Comparisons are discussed between Sympagus and other related genera in the tribe Acanthocinini. Characterizations, color images, and a key to all Sympagus species are provided.